The Decision Of Pasar Jiwa Innovation Adoption In The Early Prevention Of Mental Health Issues At The Bubakan Health Center, Pacitan Regency - Hendro Harmoko; Kristina Setyowati; Rino Ardhian Nugroho (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2023)
The research aims to analyze the stages of adopting the PaSar Jiwa innovation in the early prevention of mental health issues to address treatment gaps and social stigma. The method used is qualitative descriptive with the data analysis technique of the Miles and Huberman model. Data validity through triangulation technique, using data collection methods such as interviews, observations, and documentation. Research informants are doctors, nurses, and community health workers in the Bubakan Health Center area, selected through purposive sampling. Meanwhile, the informants for innovation adopters are selected using the accidental tal sampling technique. The research findings are as follows: Knowledge stage: 1) Indicator of knowledge about the existence of innovation. This indicator is influenced by two variables: individuals and communication behavior. The individual variable includes knowledge of solving mental health problems and cost savings. The communication behavior variable involves insufficient socialization to reach all community members. 2) Indicator of knowledge in using the innovation correctly. This indicator is influenced by individual variables indicating that handling is going well, while communication behavior is still limited due to a lack of human resources. 3) Indicator of knowledge about the functional principles of how and why the innovation works. This indicator is influenced by individual variables, where the implementers follow guidelines in carrying out the functions of the innovation. Persuasion stage: Characteristics of the innovation are influenced by four variables: 1) Relative advantage: measures comfort and satisfaction. The PaSar Jiwa innovation affects patient quality, making it advantageous. 2) Compatibility: measures consist of consistthe ency of values and adopters' needs for patient healing solutions.3) Trialability: influenced by the extent to which the innovation is gradually tested, facilitating adoption. 4) Observability: influenced by how visible the innovation is to others. Demonstrated through patient improvements, motivating adoption. Complexity does not affect this stage. Decision stage: Partial adoption of the innovation occurs, leading to quicker acceptance as adopters decide to receive the innovation. Implementation stage: The innovation is gradually tested despite uncertainty. Confirmation stage: Support and attitude of implementers/adopters confirm the sustainability of the innovation. Research suggests developing alternative methods to address the lack of mental health human resources. This could involve group discussions for adopters/patients, organized in each village with the involvement of community health workers and family members. Family support as listeners is crucial for individuals experiencing mental health disorders.